RuangGuru community as a reflection of future learning in time of COVID-19 - Chinmi, Maichel; Marta, Rustono Farady; Jarata, Jesus Rafael Boado (Jurnal Studi Komunikasi, 2021)
An effort to educate the people of a nation is a glorious educational goal, where intelligence is not only intellectually but a deeper meaning of intelligence itself. COVID-19 period is a genuinely uplifting meaning of the education itself. RuangGuru, an education-based application, provides solutions for Indonesians with free online schools. The researchers would like to see the shifting of meaning for a community who has used this application during COVID-19. The theory of Social Actions Media Studies was used to see the change in meaning. We also used the reception analysis method by Stuart Hall to classify the interviews' results into three categories, pro, contra, or neutral. The results indicate a shift in meaning due to the interpretation process by RuangGuru community, which is also influenced by local culture, on transition and future education is perceived.